Effects of cadmium on the growth, muscle composition, digestion, gene expression of antioxidant and lipid metabolism in juvenile tilapia (Oreochromis niloticus) - Zhang, Qin; Xie, Yi; Qin, Rongxin; Huang, Enhao; Zhang, Ziqi; Zhou, Jiang; Liu, Dongsheng; Meng, Liuqing; Liu, Yongqiang; Tong, Tong (Frontiers in Marine Science, 2024)
Cadmium could induce various degrees of harm to aquatic organisms. A 30-day feeding trial was conducted to investigate the effects of cadmium on growth, muscle composition, digestive enzyme activity, gene expression of antioxidants and lipid metabolism in juvenile genetic improvement of farmed tilapia (GIFT, Oreochromis niloticus, Initial weight: 21.36 ± 0.24 g). Four cadmium concentrations of aquaculture water were designed: 0, 0.2, 0.4, and 0.6 mg/L Cd 2+ . The main results are as follows:Compared with the control group (0 mg/L Cd 2+ ), the weight gain rate (WGR), specific growth rate (SGR), daily growth index (DGI), and spleen index (SI) of juvenile GIFT under cadmium stress were significantly decreased (p < 0.05). The contents of crude protein and crude lipid in muscle were significantly decreased (p < 0.05), and the ash was significantly increased (p < 0.05). The activities of trypsin, lipase, and α-amylase in the intestinal were significantly decreased (p < 0.05). The relative expression levels of carnitine palmityl transferase 1 (cpt-1), peroxisome proliferator-activated receptor α (pparα), pparγ, hormone-sensitive lipase (hsl), lipoprotein lipase (lpl), malate dehydrogenase (mdh), leptin (lep), fatty acid synthetase (fas), cholesterol response element binding protein 1 (srebp1), squalene cyclooxygenase (sqle), and stearoyl-CoA desaturase (scd) genes in liver were significantly decreased (p < 0.05). The relative expression levels of catalase (cat), superoxide dismutase (sod), glutathione Stransferase (gst), and glutathione peroxidase (gsh-px) genes in the liver were significantly decreased (p < 0.05). In conclusion, exposure to cadmium stress could impact growth, muscle composition, digestive enzyme activity, gene expression of antioxidant and lipid metabolism in juvenile GIFT.